أمننة الهجرة في سياسات الاتحاد الأوروبي: دراسة في تأثير الهجرة على الأمن الأوروبي - بلعربي, علي (جامعة الوادي University of Eloued, 2019)
ملخص: تناولت هذه الدراسة علاقة الهجرة بالأمن في سياسات الاتحاد الأوروبي، وذلك من خلال تبيان كيف تطورت الهجرة إلى قضية أمنية في أوروبا منذ ثمانينيات القرن العشرين، وإلى غاية السنوات القليلة الماضية، حيث عملت النخب السياسية والبيروقراطية في الاتحاد الأوروبي طوال هذه الفترة على تسييس قضية الهجرة ومن ثَمّ أمننتها عن طريق خطاب يعتبر الهجرة كواحدة من أخطر التهديدات الأمنية التي تشكل تحدياً حقيقيا للحكومات والمجتمعات الأوروبية على حد سواء، حيث أصبح يُنظر للهجرة كسبب لعدم الاستقرار وانعدام الأمن في أوروبا، وأضحت مسؤولة عن الكثير من المشاكل الاجتماعية والاقتصادية، كالمساس بالهوية والرفاه الاقتصادي للشعوب الأوروبي. تهدف هذه الدراسة إلى تبيان تأثير الهجرة على الأمن الأوروبي بالاعتماد على أفكار مدرسة كوبنهاغن كإطار تحليلي خاصة تلك المتعلقة بإعادة تعريف الأمن وتوسعه إلى أبعاد جديدة، مع التركيز على نظرية الأمننة عند " Ole Weaver ". Abstract: This study examines the relationship of migration to security in EU policies by showing how migration has devoloped into a security issue in Europe since the 1980s and until the last few years. During this period, political elites and bureaucrats in the EU have politicized the issue of migration and secured it through a speech that considers migration as one of the most serious security threats that pose a real challenge to both governments and European communities. Migration is seen as a cause of instability and insecurity in Europe and has become responsible for many Social and economic problems, such as threatening the identity and economic well-being of European communities. The aim of this study is to illustrate the impact of migration on European security drawing on Copenhagen School's ideas as an analytical framework especially those related to redefining security and extending it to new dimensions with focusing on the Ole Weaver theory of securization.
The Securitization Of Immigration At The Eu Policies: Study On The Impact Of Immigration On European Security
Keywords: مدرسة كوبنهاغن؛ الأمن؛ الأمننة؛ الهجرة؛ الاتحاد الأوروبي؛ التهديد؛ الأمن الأوروبي; Copenhagen School; Security; Securitization; Migration; European Union; Threat; European Security